PENGGUNAAN MEDIA KARTU HURUF PELANGI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI OESAPA KECIL 2 - Nome, Scolastika Vinsensia; Djuli, Labu; Sampe, Markus (Universitas Nusa Cendana, 2024)
This research was carried out at SDN Oesapa Kecil 2, Kupang City with the aim of improving initial reading skills using rainbow letter card media. This type of PTK research is carried out in the stages of planning, implementation, observation, and reflection. The research subjects were 25 class I students. Data collection in this research was carried out using observation and test techniques, and then the data obtained was processed and analyzed further using qualitative descriptive analysis techniques. Based on the pre-cycle data obtained by the researcher, there were 6 students with a percentage of 24% who had completed and 19 students with a percentage of 76% who had not completed, so the researcher needed to take action and obtain results in the first cycle of 15 students with a percentage of 60%. completed because they could recognize and pronounce letters, arrange letters into syllables and spell syllables into words, while there were 10 students with a percentage of 40% who had not completed it because the students were less active and paid less attention when the researcher explained. Furthermore, in cycle II there was an increase, namely 22 students with a completion percentage of 88%, which means teachers were starting to be able to overcome the deficiencies that occurred in cycle I. The percentage increase in student learning outcomes from cycle I to cycle II was 28%. So using rainbow letter card media can improve the initial reading skills of class I students at SDN Oesapa Kecil 2, Kupang city